Monocyte to HDL cholesterol ratio is associated with discharge and 3-month outcome in patients with acute intracerebral hemorrhage - You, Shoujiang; Zhong, Chongke; Zheng, Danni; Xu, Jiaping; Zhang, Xia; Liu, Huihui; Zhang, Yanlin; Shi, Jijun; Huang, Zhichao; Cao, Yongjun; Liu, Chun-Feng (Journal of the neurological sciences, 2017)
Monocyte and monocyte to high-density lipoprotein ratio (MHR) recently emerged as markers of inflammation and have been reported to be novel prognostic indicators of cardiovascular diseases. We investigated the association of monocyte and MHR with hospital discharge and 3-month outcome after acute intracerebral hemorrhage (ICH). A total of 316 patients with acute ICH were enrolled from November 2011 to March 2014. Demographic characteristics, lifestyle risk factors, medical history, admission laboratory parameters, and monocyte level were recorded. Clinical outcome was disability or death (defined as having a modified Rankin Scale score≥2) upon discharge or at 3months. 202 patients (63.9%) experienced disability or death at hospital discharge, and 176 patients (55.7%) at 3months post-ICH. Admission monocyte level was associated with clinical outcome at 3months (adjusted OR, 4.17; 95% CI, 1.45–12.00; P-trend=0.028) when highest and lowest quartiles were compared. However, no significant association was found between monocyte and discharge outcome (P-trend=0.102). Compared to the lowest category of MHR, the highest category was associated with a 3.87-fold increase in the odds of disability or death at discharge (95% CI, 1.17–12.76; P-trend=0.045) and 3.08-fold increased odds of disability or death at 3-month (95% CI, 1.05–9.08; P-trend=0.024). In patients with acute ICH, higher MHR was associated with increased risk of disability or death at discharge and at 3months post-ICH, however higher monocyte was only associated with increased risk of 3-month disability or death. •Prognostic significance of monocyte to HDL cholesterol ratio (MHR) in patients with ICH•A high MHR was independently associated disability or death at hospital discharge after acute ICH.•A high MHR was also associated disability or death at 3months after acute ICH.•A high monocyte was independently associated disability or death at 3months post-ICH.